2002
DOI: 10.1097/00004770-200206000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Apical Leakage of Five Root Canal Sealers After One Year of Storage

Abstract: A fluid transport model study was used to compare the sealing ability of five root canal sealers (AH26, AH Plus, Apexit, Diaket, and Ketac-Endo) on 60 single-rooted teeth after 1 yr of storage. The root canals were prepared with Gates Glidden drills by using a step-back technique before lateral condensation of gutta-percha with the tested sealers. The specimens were stored in saline solution for 1 yr at 37 degrees C. The leakage was measured by the movement of an air bubble in a capillary glass tube connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 11 publications
1
41
0
11
Order By: Relevance
“…This was done to demonstrate the microleakage measurement after long period, because the relative differences between the materials change over time, and this change has a clinical relevance. 23 The results demonstrated the least leakage of dye with AH Plus sealer followed by Endoflas FS, Acroseal and Endomethasone N. There was statistically significant difference between the leakages of Endomethasone N with other three groups. Sung-Eung Yang et al 24 performed an in vitro evaluation of the sealing ability of different root canal sealers using an anaerobic bacteria leakage model with Prevotella nigrescens.…”
Section: Discussionmentioning
confidence: 76%
“…This was done to demonstrate the microleakage measurement after long period, because the relative differences between the materials change over time, and this change has a clinical relevance. 23 The results demonstrated the least leakage of dye with AH Plus sealer followed by Endoflas FS, Acroseal and Endomethasone N. There was statistically significant difference between the leakages of Endomethasone N with other three groups. Sung-Eung Yang et al 24 performed an in vitro evaluation of the sealing ability of different root canal sealers using an anaerobic bacteria leakage model with Prevotella nigrescens.…”
Section: Discussionmentioning
confidence: 76%
“…Predictable clinical results have been reported with the use of gutta-percha points and epoxy resinbased root canal sealers (33) . There is an increasing interest in the use of methacrylate resin-based sealers (containing urethane dimethacrylate -UDMA) (2) , because these materials can be used with dentin adhesives for bonding to intraradicular dentin.…”
Section: Discussionmentioning
confidence: 99%
“…5,[7][8][9]11,18 AH Plus, an epoxy-resin based sealer used with gutta-percha, was selected for this study based on the good sealing results found in the literature. [5][6][7][8][9][10][11] This sealer also has good adhesion to dentin which could enhance its sealing ability. 3,22 The release of new materials demands research about their different properties.…”
Section: Discussionmentioning
confidence: 99%
“…4 AH Plus is a well established resin-based sealer and has good sealing properties. [5][6][7][8][9][10][11] Recently, Resilon, a new thermoplastic, filled polymer has been introduced and has the potential to challenge gutta-percha as a root filling material. 12,13 This material is used with Epiphany, a dual-cured resin sealer and a self-etching primer and forms a single monoblock in the root canal system.…”
Section: Introductionmentioning
confidence: 99%